THE EFFECTIVENESS OF CONTINUOUS AUDITING IMPLEMENTATION: DEVELOPING AUTOMATED AUDIT SYSTEMS FOR FRAUD AND ERROR DETECTIONS - Antonio, Gregorius Rudy (UTSAHA: Journal of Entrepreneurship, 2022)
Continuous Auditing is a new approach that allows auditors to understand control points, control rules thoroughly and system controls and with more frequent, automated data analysis; hence increased audit relevance and reliability will ultimately improve audit quality. This paper aims to prove the effectiveness of Continuous Auditing in bridging auditing with the challenges of detecting fraud and errors. In the KKK Department Store, Continuous Auditing was proven to significantly improve the audit quality and internal control of the organization, with a very significant decrease in audit Findings in 2012 and 2013. The continuous audit Findings in 2012 decreased by 75.76% or decreased by 3,523 from the Findings in 2011 followed by a decrease in Findings of 81.44% or 3787 Findings from 2011 to 2013. Manual audit Findings also decreased very significantly by 96.19% or 733 Findings from 2011 to 2012 and a decrease of 99.74% or by 760 Findings from 2011 to 2013. This significant decrease in continuous auditing Findings was due to real-time audits, population data, not samples, and continuous improvement of parameters. Another important factor that significantly influences the effectiveness of continuous auditing is the interaction between the continuous auditing component, the owner, the internal auditor, and all related parties. Strong leadership from the owner, efficient and effective interaction from internal auditors, inherent and tight supervision and strong motivation make continuous auditing a reliable tool or method that helps management achieve its goals. Continuous Auditing has proven to be very significant in improving audit quality and organizational internal control but has proven ineffective in handling transactions involving manual transactions and collusions. This study looks at two key controls: "checking whether there is a Receiving Report made more than the date specified on the Purchase Order" and "checking whether there is a Receiving Report that is not in accordance with the authorized purchasing order". An effective solution is eliminating such manual transactions or authorizations made through systems with inherent control. This solution was implemented in 2013 and successfully resolved the issue. A continuous audit approach is an approach that is efficient and effective as well as sustainable and can provide timely signals in dealing with fraud and errors through internal control and risk mitigation.